Mexico : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that after a sharp slowdown in 2013, growth in Mexico is projected to recover to 2.4 percent this year. The strong recovery in the United States in the second quarter of 2014 has triggered a rebound in Mexico's manufacturing production and exports. In addition, construction activity is firming up, supported by a rebound of residential investment and an increase of government spending on infrastructure. Mexico's external position remains broadly consistent with fundamentals and desirable policy settings. In 2014, the current account deficit is projected to remain unchanged with an improving trade balance offset by a continued increase in factor payments.